Use of Possessive Pronouns in English and Uzbek Languages - Yangibaeva Nazira (Genius Journals, 2022)
The article describes the use of possessive pronouns in English and Uzbek languages. The peculiarities of the category of possession in languages belonging to different families have been considered
Keywords: Uzbek; English; language; possession